Regenerative Braking Concept In Ceiling Fan - Muhammad Waffiudin Bin Ab Aziz, Muhammad Waffiudin (2010)
This project investigates the characteristics of regenerative braking concept as well as study on the ceiling fan motor. With the objectives of carrying a research on regenerative braking for ceiling fan, it is important to understand the theory of regenerative braking first.